부모의 인성지향적 지도와 아동의 정서지능 간의 관계에 대한 자아탄력성의 매개효과 - 양혜연(Hye Yeon Yang); 양성은(Sun Geun Yan) (Korean Journal of child studies, 2013)
The premise underpinning this research is that cognitive evaluation is the starting point of children's emotional experience. It then went on to investigate how parents' person-oriented guidance affects children's emotional intelligence. Additionally, children's ego-resilience was analyzed as a variable that affects children's emotional intelligence and as a mediator between parents' person-oriented guidance and children's emotional intelligence. A purposive sampling was conducted in 4 elementary schools in metropolitan areas and made use of 466 students in 4th and 5th grade as research subjects. The results are summarized as follows：firstly, the more frequently parents used person-oriented guidance, the more children exhibited higher levels of ego-resilience and emotional intelligence. Secondly, vitality, peer relations, optimism, curiosity, emotional regulation, maternal person-oriented guidance were found to affect emotional intelligence in the order of relative significance of that influence. Thirdly, children's ego-resilience was found to intermediate parents' person-oriented guidance and children's emotional intelligence. In conclusion, individual children's evaluations of parental verbal stimuli was found to influence children's emotional intelligence, especially more significantly through the mediation of children's ego-resilience.